Characteristics and mechanism of persulfate activated by natural siderite for water disinfection. Issue 3 (19th August 2022) - Li, Guo-Qiang; Wang, Chaoyi; Zhang, Yingying; Wan, Hongyou; Dou, Ming; Xu, Hongbin
Abstract: In this study, low-cost siderite was used to activate peroxydisulfate (PDS, S2 O8 2- )-inactivated Enterococcus faecalis to study the inactivation characteristics and mechanism of siderite/PDS. The results showed that the siderite/PDS had a better inactivation effect on Enterococcus faecalis at pH 3. The sterilization effect increases with the increase of siderite dosage, PDS concentration and temperature. The inactivation rate is decreased with the increase of initial bacterial concentration. Inorganic ions and natural organic matter (NOM) can inhibit the inactivation effect of this technology, and the inhibition intensity is NOM > HCO3 − > NO3 − . The free radical quenching test shows that HO is the main oxidizing substance in the sterilization process of siderite/PDS technology. In addition, the main disinfection mechanism is highly reactive oxygen species destroying the cell wall of bacteria and releasing organic compounds in cells. After siderite was reused for four times, simply washing siderite would recover almost 80% of the removal of Enterococcus faecalis in siderite/PDS, indicating that siderite has the potential of recycling. HIGHLIGHTS: Enterococcus faecalis (Gram-positive bacteria), a typical disinfection residue bacteria, was used as the indicator microorganism. The economic and efficient natural siderite was used as the activator of persulfate, and the reusability and structural stability of the recovered siderite are also analyzed. Graphical Abstract